ANALYSIS OF MATHEMATICS BASED LEARNING PROBLEM WITH SCIENTIFIC APPROACH IN EDUCATOR CLASS XI MIPA IN SMA NEGERI 7 MAKASSAR - Rahmah, Rahmah (Sains Global Institut, 2019)
This study aims to describe Mathematical Problem-Based Learning with a scientific approach on educators class XI MIPA in SMA Negeri 7 Makassar. The result of the research shows that: 1) In developing RPP, mathematics teacher of XI MIPA class in SMA Negeri 7 Makassar is still arranged in collaboration, the reason is still lack of understanding about RPP development mechanism in accordance with Permendikbud Number 22 year 2016. 2) Problem Based Implementation Process mathematics with a scientific approach in the class XI MIPA in SMA Negeri 7 Makassar has not run optimally. This is seen in the indicators at each stage of the core activity on the aspect of the educator applying the scientific approach, and on the application aspects of Problem Based Learning has not been fulfilled. The constraints faced by educators are the difficulty of changing the views of educators who are still a little carried away with the curriculum before the Curriculum 2013, the lack of knowledge and the ability of educators in facilitating the process of Problem Based Learning with scientific approach, and time management in implementing the process of Problem Based Learning Implementation with scientific approach.